2023
DOI: 10.1101/2023.11.07.566052
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The impact of kit, environment and sampling contamination on the observed microbiome of bovine milk

C. J. Dean,
Y. Deng,
T. C. Wehri
et al.

Abstract: Contaminants can easily outnumber bacteria that originate within the milk itself, milk microbiome research currently suffers from a critical knowledge gap; namely, does non-mastitis bovine milk contain a native microbiome? In this study, we sampled external and internal mammary epithelium, stripped and cisternal milk, used numerous negative controls to identify potential sources of microbial contamination. Two algorithms were used to mathematically remove this contamination and to track potential movement of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…The existence of a commensal microbiota on the bovine teat canal and teat skin is widely acknowledged [83,84]. However, the demonstration of a commensal bovine milk microbiome has been disputed by methodological issues, sampling difficulty, and a lack of consistency among studies [85,86]. Previous studies have shown that diet has a direct impact on the gut, rumen, and milk microbiota of bovines [87][88][89].…”
Section: Microbiological Qualitymentioning
confidence: 99%
“…The existence of a commensal microbiota on the bovine teat canal and teat skin is widely acknowledged [83,84]. However, the demonstration of a commensal bovine milk microbiome has been disputed by methodological issues, sampling difficulty, and a lack of consistency among studies [85,86]. Previous studies have shown that diet has a direct impact on the gut, rumen, and milk microbiota of bovines [87][88][89].…”
Section: Microbiological Qualitymentioning
confidence: 99%